Association of betatrophin amounts with 25-(OH)D levels in patients with gestational diabetes mellitus. Issue 16 (23rd April 2021) - Yang, Fuyan; Yang, Wenfa; Wang, Guohua; Liu, Yaqiong; Jin, Jun
Abstract : Abstract: To determine the association of betatrophin amounts with 25-(OH)D levels in gestational diabetes mellitus (GDM) patients, and to provide new targets for the prevention and treatment of GDM. This study included 40 GDM patients (GDM group) and 37 healthy pregnant women (control group). Betatrophin, 25-(OH)D, fasting blood glucose (FBG), HbA1c, hsCRP, and FINS levels in peripheral blood, as well as betatrophin and 25-(OH)D amounts in cord blood, were measured. Then, associations of betatrophin levels with 25-(OH)D amounts and other indexes were determined. Maternal ( P  = .011) and cord ( P  = .022) blood betatrophin levels were significantly lower in the GDM group compared with control group. Cord blood betatrophin levels were higher compared with maternal blood amounts in both the GDM and control groups (both P  = .000). Serum betatrophin levels were positively associated with 25-(OH)D levels ( r  = 0.677, P  = .000), but negatively associated with hsCRP ( r  = −0.335, P  = .037) and HOMA-IR ( r  = −0.346, P  = .031) levels in the GDM group. Fetal weight was higher in the GDM group compared with control group ( P  = .023), and negatively associated with cord blood betatrophin amounts in the GDM group ( r  = −0.342, P  = .031). However, cord blood betatrophin levels were not significantly associated with body length, Apgar score, and cord blood 25-(OH)D levels in the GDM group (all P  > .05). Serum betatrophin and 25-(OH) D levels were positively associated in women with GDM, and both significantly lower compared with control values. Fetal weight was higher in the GDM group and associated with cord blood betatrophin. These findings provide insights into developing new predictive biomarkers or therapeutic targets for GDM.